FOXP1 is associated with oncogenesis and clinical outcomes in hematologic malignancies - Wen, Xiang-mei; Xu, Zi-jun; Ni, Hao-xi; Liu, Su-wan; Jin, Ye; Zhao, Wei; Luo, Shu-yu; Fang, Yuan-yuan; Mao, Zhen-wei; Lin, Jiang; Qian, Jun (Frontiers in Immunology, 2025)
Depending on the cellular context and cancer type, FOXP1 functions as an oncogene or a tumor suppressor. However, the clinical role of FOXP1 in hematologic malignancies has not been studied comprehensively. This study systematically analyzed the association of FOXP1 expression with clinical outcomes, including prognosis and immunotherapeutic response, as well as biological functions across a range of hematological cancers. Our findings demonstrated that FOXP1 expression was dysregulated in several hematological malignancies and was associated with poor prognosis. FOXP1 was highly expressed in acute myeloid leukemia (AML). Methylation of the FOXP1 promoter was significantly reduced in patients with AML compared to the healthy control subjects and those with myelodysplastic syndromes. FOXP1 promoter methylation showed an inverse relationship with FOXP1 gene expression in AML. Moreover, FOXP1 expression was associated with the tumor infiltration of B cells, natural killer cells, and T cells, as well as the cytolytic score across various hematologic malignancies. Our data showed that FOXP1 expression was a promising biomarker for predicting responses to immunotherapy in AML patients. Functionally, the knockdown of FOXP1 demonstrated antileukemic effects, including reduced AML cell proliferation and cell cycle arrest in the G1-S phase. In conclusion, this study systematically investigated the role of FOXP1 across a spectrum of hematological malignancies and demonstrated that FOXP1 was a promising prognostic biomarker and a potential therapeutic target in AML and other hematological malignancies.